2020
DOI: 10.1371/journal.pone.0233132
|View full text |Cite
|
Sign up to set email alerts
|

Traditional milk transformation schemes in Côte d’Ivoire and their impact on the prevalence of Streptococcus bovis complex bacteria in dairy products

Abstract: The Streptococcus bovis/Streptococcus equinus complex (SBSEC) and possibly Streptococcus infantarius subsp. infantarius (Sii) are associated with human and animal diseases. Sii predominate in spontaneously fermented milk products with unknown public health effects. Sii/SBSEC prevalence data from West Africa in correlation with milk transformation practices are limited. Northern Cô te d'Ivoire served as study area due to its importance in milk production and consumption and to link a wider Sudano-Sahelian pasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Streptococcus spp. are widely distributed bacteria in food fermentations, and they have great importance in medicine and industry (31)(32)(33)(34). Several streptococci are commensal in mammals; however, some can also cause illnesses ranging from mild to acute.…”
Section: Discussion Proteome Dynamics In Pozol Fermentationmentioning
confidence: 99%
“…Streptococcus spp. are widely distributed bacteria in food fermentations, and they have great importance in medicine and industry (31)(32)(33)(34). Several streptococci are commensal in mammals; however, some can also cause illnesses ranging from mild to acute.…”
Section: Discussion Proteome Dynamics In Pozol Fermentationmentioning
confidence: 99%
“…Similarly, a study from Mali showed that handwashing before milking was rare, and the person milking would soak his hands in the already collected milk to lubricate the teat [ 53 ]. A study conducted in Northern Côte d’Ivoire also found a lack of handwashing and cleaning of udders before milking, as well as the storage of milk in unsuitable containers, such as those previously used for oil or chemicals and those that have not been properly cleaned [ 54 ]. Millogo et al [ 49 ] reported that milk was collected in plastic buckets or calabashes in peri-urban areas of Burkina Faso.…”
Section: Food Safety Hazards In the Dairy Value Chainmentioning
confidence: 99%
“…Millogo et al [ 49 ] reported that 21 out of 22 farmers had no cooling system in Burkina Faso, and 95.2% of participants never cooled milk after collection in Senegal [ 35 ]. In Northern Côte d’Ivoire, milk was stored for more than two hours after collection at ambient temperatures of approximately 30 °C [ 54 ].…”
Section: Food Safety Hazards In the Dairy Value Chainmentioning
confidence: 99%
See 2 more Smart Citations